HIJRAH DAN KAITANNYA DENGAN SEMANGAT KEBANGSAAN - Muhith Muhammad Ishaq (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
This study aims to interpret hijrah and its description with the spirit of nationalism. This qualitative research uses literature and interprets textually. The data used are written websites, journals, books, Al-Qur'an, Hadith and other library sources. This research concludes that hijrah can be interpreted as an effort to build a dignified society built by various ethnic groups who have a shared vision with love and faith, they work together to achieve their goals in the abundance of Allah SWT's grace and pleasure. Hijrah is an important process in building the spirit of nationalism and nationalism.